PERILAKU KONSUMEN TERHADAP LEVEL PENGGUNAAN GULA AREN (Arenga piñnata) - Dedi Dedi; Ristina Siti Sundari; D Yadi Heryadi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
People's livelihoods in the agricultural sector urgently need public sector services. The role of agricultural extension workers is to help increase food production and development. Counseling in Culamega District, Tasikmalaya Regency, was carried out by PNS extension workers, THL (Freelance) extension workers, and self-help extension workers. One of the supporters of increasing the performance or development of organic tea farmers in Culamega District is that independent extension workers are responsible for helping extension workers and farmers to strengthen the relationship between extension workers and farmers. From land cultivation to processing results, organic tea is a tea plant that uses organic ingredients without mixing chemicals or pesticides. Fertilization uses fertilizer based on goat manure, roasted husks, and liquid organic fertilizer. This study aimed to determine the effect of the role of independent extension workers on the development of organic products in Cipicung Village. The results of this study indicated that independent extension agents play a role in the development of organic tea products in Cipicung Village, Culamega District.